2008
DOI: 10.1097/brs.0b013e318178e5c8
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Three Dimensional Morphometry of the Lateral Atlantoaxial Articular Surfaces

Abstract: There seems to be a strong relationship between the anatomic features of the lateral articulating surfaces of atlas and axis. Differences in the orientation of joint surfaces to the frontal plane may be related to deviations from the neutral position. This issue raises the problem of the definition of three-dimensional-neutral joint positions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 20 publications
1
20
1
Order By: Relevance
“…Konig et al [17] has used a grid system to measure the dimensions which might have lead to higher values. Cattrysse et al [18] evaluated pairs of atlas and axis vertebrae from same spine and found that the C1 IAF has lower APD than the SAF of C2. The TD observed by Kandziora et al [19] , Gomez-Olivencia et al [20] and Cattrysse et al [18] have higher values than our study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Konig et al [17] has used a grid system to measure the dimensions which might have lead to higher values. Cattrysse et al [18] evaluated pairs of atlas and axis vertebrae from same spine and found that the C1 IAF has lower APD than the SAF of C2. The TD observed by Kandziora et al [19] , Gomez-Olivencia et al [20] and Cattrysse et al [18] have higher values than our study.…”
Section: Methodsmentioning
confidence: 99%
“…Cattrysse et al [18] evaluated pairs of atlas and axis vertebrae from same spine and found that the C1 IAF has lower APD than the SAF of C2. The TD observed by Kandziora et al [19] , Gomez-Olivencia et al [20] and Cattrysse et al [18] have higher values than our study. Whereas Sengul et al [6] has lower value, Konig et al [17] is closest.…”
Section: Methodsmentioning
confidence: 99%
“…Cattrysse E [19] and et al did an anatomical study of 20 atlas vertebrae and found the mean value of the length of inferior articular facet of atlas vertebrae to be 17.7 mm. Gokflin Fiengul [7] and et al in their study found the mean values of the length and width of inferior articular facet of atlas vertebrae to be 17.3 mm and 14.6 mm respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a new ex vivo approach is presented for the direct estimation of cortical bone thickness using a three‐dimensional digitizing stylus (Microscribe 3DX® ‐ Immersion Corporation ‐ USA) on transverse sections of distal and proximal tibia. This approach has been used in previous morphological studies of the upper cervical spine (Cattrysse et al, 2007, 2008). The intra and interobserver reproducibility of this approach are analyzed in order to estimate the appropriateness of cortical bone surface estimation by direct digitization to serve as a gold standard in further studies validating automated or semiautomated measurements using CT or MR.…”
Section: Introductionmentioning
confidence: 99%